Genome wide transcriptome analysis reveals ABA mediated response in Arabidopsis during gold (AuCl−4) treatment - Shukla, Devesh; Krishnamurthy, Sneha; Sahi, Shivendra V. (Frontiers in Plant Science, 2014)
The unique physico-chemical properties of gold nanoparticles (AuNPs) find manifold applications in diagnostics, medicine and catalysis. Chemical synthesis produces reactive AuNPs and generates hazardous by-products. Alternatively, plants can be utilized to produce AuNPs in an eco-friendly manner. To better control the biosynthesis of AuNPs, we need to first understand the detailed molecular response induced by AuCl4- In this study, we carried out global transcriptome analysis in root tissue of Arabidopsis grown for 12- hours in presence of gold solution (HAuCl4) using the novel unbiased Affymetrix exon array. Transcriptomics analysis revealed differential regulation of a total of 704 genes and 4900 exons. Of these, 492 and 212 genes were up- and downregulated, respectively. The validation of the expressed key genes, such as glutathione-S-transferases, auxin responsive genes, cytochrome P450 82C2, methyl transferases, transducin (G protein beta subunit), ERF transcription factor, ABC, and MATE transporters, was carried out through quantitative RT-PCR. These key genes demonstrated specific induction under AuCl4- treatment relative to other heavy metals, suggesting a unique plant-gold interaction. GO enrichment analysis reveals the upregulation of processes like oxidative stress, glutathione binding, metal binding, transport, and plant hormonal responses. Changes predicted in biochemical pathways indicated major modulation in glutathione mediated detoxification, flavones and derivatives, and plant hormone biosynthesis. Motif search analysis identified a highly significant enriched motif, ACGT, which is an abscisic acid responsive core element (ABRE), suggesting the possibility of ABA- mediated signaling. Identification of abscisic acid response element (ABRE) points to the operation of a predominant signaling mechanism in response to AuCl4- exposure. Overall, this study presents a useful picture of plant-gold interaction with an identification of candidate genes invol